An Optimal Stock Market Portfolio Proportion Model Using Genetic Algorithm - Wahyono Wahyono; Chasandra Puspitasari; Muhammad Dzulfikar Fauzi; Kasliono Kasliono; Wahyu Sri Mulyani; Laksono Kurnianggoro (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2018)
To reduce the amount of loss due to investment risk, an investor or stockbroker usually forms an optimal stock portfolio. This technique is done to get the maximum return of investment on shares to be purchased. However, in forming a stock portfolio required a fairly complex calculations and certain skills. This work aims to provide an alternative solution in the problem of forming the optimal and efficient stock portfolio composition by designing a system that can help decision making of investors or stockbrokers in preparing stock portfolio in accordance with the policy and risk investment. In this work, determination of optimal stock portfolio composition is constructed by using Genetic Algorithm. The data used in this work are the 4 selected stocks listed on the LQ45 index in 2017. Meanwhile, the calculation of profit and loss rate utilizes a single index model theory. The efficiency of the algorithm has been examined against the population size and crossover and mutation probabilities. The experimental results show that the proposed algorithm can be used as one of solutions to select the optimal stock portfolio.